Breaking the Silence: Group Discussions, and the Adoption of Welfare-Improving Technologies - Silvia Castro; Clarissa Mang (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Social pressure and stigma can hinder the adoption of available technologies, especially in the context of sensitive health issues. We run a field experiment on the take-up of menstrual products in Bangladesh and test a discussion-based intervention in a work setting. We vary participation in group discussions designed to break the silence around menstruation, where colleagues share their personal experiences. We find positive effects on the willingness to pay for a known menstrual product (sanitary pads) and on the adoption of a new technology (anti-bacterial menstrual underwear). Our results show changes in restrictive social norms around purchasing the products and lower perceived stigma around menstruation in general.
Keywords: D91; I12; I15; O12; 330; social norms; social pressure; stigma; technology adoption; group discussions; menstrual health management; menstrual hygiene; adverse health behavior